2022
DOI: 10.1080/21655979.2022.2071010
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the effects of microRNA-145-5p and phosphoserine aminotransferase 1 in colon cancer

Abstract: Previous studies manifested that microRNA-145-5p is pivotal in the development of various cancers. Nevertheless, the potential function of microRNA-145-5p in colorectal cancer remains unclear. This study attempted to investigate the potential role and possible mechanism of microRNA-145-5p in colon cancer. MicroRNA-145-5p and phosphoserine aminotransferase 1 (PSAT1) levels in colon cancer cells were assayed via quantitative reverse transcription polymerase chain reaction (qRT-PCR). Cell proliferation and cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Relevant studies showed that miRNA can target the expression of proto-oncogenes or tumor suppressor genes to regulate the biological behavior of tumors [ 21 ]. For example, in colon cancer cell lines, miRNA-145-5p can regulate the expression of phosphoserine aminotransferase 1 (PSAT1) and inhibit the proliferation of colon cancer cells [ 22 ]. In addition, miR-451 was found to inhibit the epithelial mesenchymal transition (EMT) of glioma cells, as well as its invasion and metastasis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies showed that miRNA can target the expression of proto-oncogenes or tumor suppressor genes to regulate the biological behavior of tumors [ 21 ]. For example, in colon cancer cell lines, miRNA-145-5p can regulate the expression of phosphoserine aminotransferase 1 (PSAT1) and inhibit the proliferation of colon cancer cells [ 22 ]. In addition, miR-451 was found to inhibit the epithelial mesenchymal transition (EMT) of glioma cells, as well as its invasion and metastasis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal cancer is one of the most important cancers worldwide. The incidence of digestive tract cancer in China is rising rapidly, and its morbidity and mortality rates are closely behind those of lung cancer, which has the highest incidence in China (17,18). Early gastrointestinal cancers include rectal cancer, biliary tract cancer, gastric cancer, esophageal cancer, pancreatic cancer, colorectal cancer, and hepatocellular carcinoma (19).…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is regulated by p53 and other transcriptional factors [ 56 ]. The tumor-suppressive role of miR-145 has been suggested in diverse types of cancers [ 57 , 58 , 59 ], such as breast cancer [ 60 ], gastric cancer [ 61 ], bladder cancer [ 62 ], colorectal cancer [ 63 , 64 ], and ovarian cancer [ 65 ]. It has been sponged by multiple circular RNAs and lncRNAs, leading to deregulation of downstream gene targets ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%